Biodiversidad de grupos funcionales de microorganismos asociados a suelos bajo cultivo de papa, ganadería y páramo en el Parque Nacional Natural de Los Nevados, Colombia (2016)
This article describes the isolation of 1,060 microbial morphotypes (bacteria and fungi) nitrogen fixing, phosphate solubilizing and cellulolytics of soils under potato crop, livestock and páramo with the least human intervention possible from the municipality El Bosque in Los Nevados National Natural Park. For each morphotype the taxonomic identification using molecular markers, the functional group to which it belongs (nitrogen fixing, phosphate solubilizing or cellulolytic), and the georeferenced location of isolation and associated land use was reported. This work contributes to the characterization of the poorly known biodiversity of bacteria and fungi from the extreme environmental conditions of Colombian páramos.